Implementasi Digital Marketing pada Unit Usaha Ritel Koperasi Syariah dalam Meningkatkan Volume Penjualan - Siti Ayu Juliyah; Dini Selasi (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2026)
This study aims to analyze the implementation of digital marketing in Sharia cooperative retail business units to increase sales volume. Advances in information technology have driven changes in consumer behavior, leading to an increasing reliance on digital media for product information and transactions. This situation requires Sharia cooperatives to adapt through the implementation of effective digital marketing strategies. This study employed a qualitative method with a case study approach. Data were obtained through observation, in-depth interviews, and documentation. The research informants consisted of cooperative administrators, retail business unit managers, and consumers who interacted with the cooperative's digital marketing media. Data analysis techniques used the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing. The results show that the implementation of digital marketing through social media, WhatsApp Business, and digital promotions can expand market reach, enhance interaction with consumers, and drive increased sales volume. However, obstacles remain, including limited human resources and consistency in digital content management. Therefore, improving the digital competency of cooperative managers is necessary to optimize digital marketing strategies.